2013
DOI: 10.1371/journal.pone.0073884
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Antifungal Action of a New Polyene Macrolide Antibiotic Antifungalmycin 702 from Streptomyces padanus JAU4234 on the Rice Sheath Blight Pathogen Rhizoctonia solani

Abstract: Antifungalmycin 702, a new polyene macrolide antibiotic produced by Streptomyces padanus JAU4234, has a broad antifungal activity and may have potential future agricultural and/or clinical applications. However, the mechanism of antifungal action of antifungalmycin 702 remains unknown. Antifungalmycin 702 strongly inhibited mycelial growth and sclerotia formation/germination of Rhizoctonia solani. When treated with antifungalmycin 702, the hyphae morphology of R . solani became more irregular. The memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Biocontrols of rice sheath blight by antagonistic microorganisms including Bacillus species (Kakar et al, 2018;Peng et al, 2014;Shrestha et al, 2016), Streptomyces species inclusive of Streptomyces aurantiogriseus VSMGT1014, Streptomyces philanthi RM-1-138, and Streptomyces padanus JAU4234 (Boukaew and Prasertsan, 2014;Harikrishnan et al, 2014;Xiong et al, 2013) and Trichoderma species (Chen et al, 2015) have been reported. Recent study indicated that antifungalmycin N2 produced by Streptomyces sp.…”
mentioning
confidence: 99%
“…Biocontrols of rice sheath blight by antagonistic microorganisms including Bacillus species (Kakar et al, 2018;Peng et al, 2014;Shrestha et al, 2016), Streptomyces species inclusive of Streptomyces aurantiogriseus VSMGT1014, Streptomyces philanthi RM-1-138, and Streptomyces padanus JAU4234 (Boukaew and Prasertsan, 2014;Harikrishnan et al, 2014;Xiong et al, 2013) and Trichoderma species (Chen et al, 2015) have been reported. Recent study indicated that antifungalmycin N2 produced by Streptomyces sp.…”
mentioning
confidence: 99%
“…From ( Table 1, Molecular factors responsible for the resistance phenotype in the cell identified has been reported to include over expression of two types of efflux pumps, mutation of the target enzyme, and alteration of other enzymes in the same biosynthetic pathway as the target enzyme (53,11). Generally, azoles and polyenes actions are mainly directed against ergosterol, the major sterol of the fungal plasma membrane, which is analogous to cholesterol in mammalian cells, (13)(14). The dosing schedule may have an effect on the development of resistance (4), since patients treated with intermittent therapy were more likely to develop resistance than those treated continuously.…”
Section: Resultsmentioning
confidence: 99%
“…The depicted different levels of exposure to various antifungal agents tested may be a pointer to emergence of resistant clones of oropharyngeal yeast strains among the HIV infected patients studied. The frequency of diagnosed fungal infections is known to have risen due to increase in the number of immunosuppressed patients resulting from the AIDS epidemic and increase in the frequency of recalcitrant infections to standard antifungal therapy (13)(14), Susceptibility of isolates to antifungals varied and MIC values were significantly (p<0.05) dependent on district of sample collection. Thus, despite being treated with same guidelines by clinicians in the same TASO centres, patient's uptake and compliance to treatment guidelines were different, thus depicting different levels of exposure to antifungals agents and probable prescription pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using chemical fungicide can effectively control the severity of R. solani, however, chemical fungicide is generally considered to be among the potential health and environmental risks . Hence, to reduce the harmful effects to the environmental search for novel natural product-based fungicide, has gained attention in the past decades (Xiong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%